ANALISIS PENDEKATAN MIMETIK PADA PUISI “GAMBAR KOTA DULU” KARYA SITOR SITUMORANG - Adiwena, Maria Widhi Majesta; Munaris, Munaris; Prasetyo, Heru (Universitas Madura, 2023)
Literary works such as poetry really need to be analyze d with various approaches, one of which is the mimetic approach. The aim is to see the reality related to the literary works created and to see the truth about poetry literary works as a result of imitation or imitation. The method used in this research is descriptive qualitative method, where the data in the research is contained in the poem